Applications of distributed fiber Bragg gratings to the measurements of in-tube fluid temperature distribution. (5th February 2023) - Chen, Yunsheng; Mo, Siyi; Li, Wenzhao; Huang, Liping; Wen, Shizhe; He, Zhenhui
Highlights: A reliable method for measuring temperature distribution using distributed fiber Bragg gratings is proposed and verified. A mathematical model of heat transfer of the sealed DFBGs is established, and verified. Condensation lengths and the frequency of oscillation are obtained for a two-phase loop by the sealed DFBGs. Abstract: The temperature distribution information of the two-phase fluid inside a tube can effectively reflect the heat transfer of the fluid, which is the key information in the study of the heat transfer of flowing fluid in a tube. This article aims to develop a method for measuring the temperature distribution of fluid inside a tube based on distributed fiber Bragg gratings (DFBGs). It is more convenient than traditional measurement methods using thermocouples that are impossible to be installed to the inner tube of a double tube heat exchanger. By using a stainless steel seamless tube, ϕ1.0 × 0.2 mm in size, and a hose to seal and protect the optical fiber with Bragg grating sensors inside, we successfully shielding the stress effects from the thermal effects, and also enhance the durability of the fiber. Since the seal leads to extra thermal resistance to the DFBGs, obtaining the response performance of the sealed DFBGs to a temperature change is essential for reliable applications. The performance characterization shows that the temperature measurement repeatability of the sealed DFBGs is within 0.2 °C for a period up to 35 months. The time constants of the DFBGs are not longer than 0.25 s, capable of measuring the temperature oscillations with frequency less than 2 Hz. Comparison with commercial thermocouples supports the feasibility and the reliability that the sealed DFBGs can be used as temperature sensors. To obtain the equivalent thermal conductivity between the tube that sealed the fiber and the fiber, κ ¯ air, the response to a temperature jump was also calculated based on a simplified model, which can comprehensively reflect the heat transfer of the air inside the sealed tube and provide the reference for design optimization of a sealed FBG for dynamic measurements. Finally, the capillary tube with sealed DFBGs was placed in the condenser tube of a two-phase circulation loop to exhibit the feasibility of the steady and dynamic temperature distribution measurements of the fluid inside a tube.